Uji Antifungi Ekstrak Bayam Merah (Amaranthus tricolor L.) terhadap Pertumbuhan Candida albicans - Wenny Rahmawati; Dwi Norma Retnaningrum (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Candidiasis is starting to increase globally in line with the increase in the immunocompromised population such as people with HIV (Human Immunodeficiency Virus), diabetes mellitus, antibiotic consumption, and pregnant women. The incidence of candidiasis in pregnant women increased by 40%. Candidiasis is caused by a Candida yeast infection such as Candida albicans. Red spinach (Amaranthus tricolor L.) is a plant that has antifungal effects because it contains alkaloids, tannins, saponins, and flavonoids. The research was conducted in a laboratory experimental manner using the disc diffusion method to determine the effectiveness of red spinach (Amaranthus tricolor L.) as an antifungal against Candida albicans in vitro. Analysis of the data used is Anova One Way and Pearson correlation. Based on the results of the study, the highest inhibition zone was at a concentration of 100%, namely 16.4 mm, this means that red spinach (Amaranthus tricolor L.) has strong antifungal power to inhibit the growth of Candida albicans. Researchers hope that these results can be a general reference material for further research to prevent candidiasis so as to improve maternal health rates.